A row-action alterative to the space-alternating generalized expectation-maximization algorithm for image reconstruction in positron emission tomography - Zhu Hongqing; Shu Huazhong; Luo Limin; Zhou Jian (2004 IEEE 11th Digital Signal Processing Workshop : & 2nd [sic] IEEE Signal Processing Education Workshop : Taos Ski Valley, NM, 1-4 August, 2004, 2004)
The space-alternating generalized expectation (SAGE) maximization algorithm has been successfully used in image reconstruction due to its rapid convergence. In this paper, a row-action alternative to the SAGE algorithm (RASAGE) is proposed; it processes the projection data sequentially. In order to speed up the convergence rate, we process the projection lines using a special order in such a way that the sequential projection lines are independent of each other. A relaxation parameter is also used to adjust the projection data update level. Comparison of the RASAGE with SAGE algorithm shows that the former method converges faster than the latter.